Pengaruh Perencanaan Pajak dan Penghindaran Pajak terhadap Nilai Perusahaan yang dimoderasi oleh ESG - Anissa Della Ananda Putri Suhendro; Deni Darmawati (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The Indonesian tax system continues to evolve to improve efficiency and taxpayer compliance. The primary objective of this study is to analyze the effect of tax planning and tax avoidance on firm value and to examine the role of ESG as a moderating variable, thus yielding a more comprehensive understanding of tax management within the framework of sustainability and corporate governance. The study uses a quantitative research design to examine the relationship between tax planning and tax avoidance as independent variables, firm value as the dependent variable, and ESG as a moderating variable. Based on the results of the hypothesis testing, it can be concluded that tax planning has a positive effect on firm value. Tax avoidance, on the other hand, has no significant effect on firm value. Furthermore, ESG cannot moderate the effect of tax planning on firm value